Ethnobotanical inventory and traditional medicinal applications of the flora in Kutwal Haramosh Valley, District Gilgit, Pakistan - Shahab Ud Din; Abbas, Qamar; Khadim, Salim; Abbas, Pervaz; Abbas, Hasnain; Zuhra, Tehseen; Irfani, Muhammad Aqeel (Ethnobotany Research and Applications, 2024)
Background: In the Kutwal Valley Haramosh region, traditional ethnomedical knowledge and local flora are at risk due to the rise of modern medicine and rapid land conversion. Thus, the current study aims to document and explore the cultural significance of medicinal plants, emphasizing the urgent need for conservation efforts. Methods: We used semi-structured questionnaires to gather information from residents and interviewed farmers, shepherds, and elderly individuals who have traditional knowledge. Results: The study identified 91 plant species across 40 families in the local area, with Asteraceae being the predominant family, represented by 13 species. Herbs constituted 76% of the species, primarily utilizing aerial parts (29 species) and roots (20 species) in medicinal preparations, often consumed directly (35 species) or through decoction (22 species). The highest use values (1), relative frequency citation (0.9), and fidelity levels (100%) were observed for Saussurea simpsoniana, Tanacetum falconeri, Berberis lyceum, Pleurospermum brunonis, Euphorbia cornigera, and Punica granatum, indicating their paramount significance in traditional medicine. The highest Informant Consensus Factor values (1) were recorded for the community-based syndrome, immunity, stress, gastrointestinal issues, skin conditions, temperature regulation, headaches, blood disorders, infertility, and mental health. A strong positive correlation (r = 0.7699, p < 0.0001) between use values and relative frequency citation highlights the link between perceived medicinal value and local use. Conclusion: The study emphasizes the need for conservation efforts amidst threats such as overgrazing, deforestation, overexploitation, and habitat loss, and suggests further phytochemical research to validate medicinal properties. Keywords: Gilgit, Kutwal Haramosh, Ethnobotany, Medicinal plants, Conservation